2019
DOI: 10.5114/amsad.2019.86752
|View full text |Cite
|
Sign up to set email alerts
|

Can metformin stabilize PCSK9 level in stable coronary artery disease patients treated with statins?

Abstract: Introduction Proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as an important marker of cardiovascular risk and a new target for therapeutic interventions. We aimed to study the influence of metformin on the level of circulating PCSK9 in patients with stable coronary artery disease (SCAD) and type 2 diabetes (T2DM) or metabolic syndrome (MetS), receiving moderate doses of statins used in routine clinical practice. Material and methods The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Oral statins may even improve diseases not commonly associated with statin use such as psoriasis, particularly in patients with severe disease [24]. Further research has also shown that metformin may stabilize PCSK9 levels in patients with CAD treated with statins [25].…”
Section: Perspectivesmentioning
confidence: 99%
“…Oral statins may even improve diseases not commonly associated with statin use such as psoriasis, particularly in patients with severe disease [24]. Further research has also shown that metformin may stabilize PCSK9 levels in patients with CAD treated with statins [25].…”
Section: Perspectivesmentioning
confidence: 99%
“…The effects of the active forms of GLP-1 are mediated by a G protein-coupled receptor, GLP-1R, which is expressed in several sites, including enteric and vagal nerves, the stomach, pancreas, intestine, and various regions of the brain [29]. The physiological functions of GLP-1 include insulin secretion stimulation; glucagon secretion inhibition; protecting β-cells through endoplasmic reticulum stress reduction; reduction of food intake; stomach emptying reduction, thereby reducing the postprandial glucose peak; improvements in cardiomyocyte glucose utilisation, cardiac function, and cardiovascular protection [25,30,31]; and appetite suppression at the level of the hypothalamus and the promotion of weight loss [32][33][34]. Additionally, recent evidence suggests that GLP-1 RA may have a direct action (independent of central nervous system (CNS) actions) in the white adipose tissue inducing browning, enhancing lipolytic capacity and mitochondrial biogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The H3K27me3 family of demethylases contains several key family members, such as KDM7A KDM6A, and KDM6B, all of which can interact with the tri-methyl groups in their targets to specifically overcome certain factors leading to gene repression during tissue differentiation. As a compound frequently used as a nutritional supplement, metformin treatment has been reported to stabilize the level of circulating PCSK9 in stable coronary artery disease (SCAD) patients [5]. And metformin can directly act on the activation of certain key signaling pathways involved in senescence and aging, including the UTX/KDM6A pathway [15].…”
Section: P R E P R I N Tmentioning
confidence: 99%